Platelet receptors and patient responses: The contributions of Professor Stan Heptinstall to platelet research. (July 2015) - Clemetson, Kenneth J.
Abstract Stan Heptinstall's contributions to platelet research covered organising meetings at the national and European level as well as starting and maintaining the journal "Platelets". The major part of his research addressed problems of inhibition of platelet receptors and the effects of this on patient health. In particular, the effects of P2Y12 inhibitors on patients with acute cardiovascular problems were a major focus. Other studies included the effects of feverfew (Tanacetum parthenium) extracts on platelets, of direct anti-IIb/IIIa receptor (αIIbβ3) inhibitors and of prostanoids on platelet function. Recently, methods for assessing the effectiveness of platelet inhibition were investigated.